Styrene and Azo-Styrene Based Colorimetric Sensors for Highly Selective Detection of Cyanide - Agustina Eka Prestiani; Bambang Purwono (Universitas Gadjah Mada, 2017)
A novel styrene (1) and azo-styrene (2) based chemosensor from vanillin has been successfully synthesized. Sensor 1 was obtained by one step Knoevenagel condensation of Ultrasound method and sensor 2 by coupling diazo and Knoevenagel condensation reaction. Both of sensors showed high sensitivity and selectivity to detect CN- in aqueous media, even the presence of other anions, such as F-, Cl-, Br-, I-, CO32-, SO42-, H2PO4-, and AcO-. Colorimetric sensing of sensor 1 is inclined to be deprotonating of sensor binding site in the presence of cyanide and consequently improve the selectivity and sensitivity in sensing cyanide which displayed color change of sensor from yellowness to red-purple and then purple in 1 min. Sensor 2 exhibited chemodosimeter phenomenon which is caused by the nucleophilic addition of cyanide with a colour change from green to greenish-blue. The results enable to do an anion detection by a naked eye.